Self-Reported and Objectively Measured Physical Activity of Elderly Mans from Bar - Milos Kovacevic (Journal of Anthropology of Sport and Physical Education, 2018)
We did a research with a sample of 100 male respondents from Bar. A standardized IPAQ questionnaire was used as the instrument of the research, in order to find out the amount of physical activity for people aged between 50 and 69 years. From that number of respondents, 63 respondents was between 50 and 59 years, and 37 respondents between 60 and 69 years. The questionnaire consists questions about physical activity on work, in transport, at home, and during free time. The research results have shown that respondents of both groups have a low level of physical activity in transport, by the younger group 429,81MET, and by the older group 571,38MET. The same level of activity is present for free time activity by the younger group 546,2MET. A moderate physical activity are represented for free time activities by the older group 927,3MET. All the other aspects of physical activities are represented on a high level, by both groups. By comparing these two subsamples with a t-test (level of significance 0,01), it has been established that there is a statistically significant difference between these results, except for the total moderate intensity activities.